Inverse association of vitamin D3 levels with lung cancer mediated by genetic variation. (3rd May 2018) - Haznadar, Majda; Krausz, Kristopher W.; Margono, Ezra; Diehl, Christopher M.; Bowman, Elise D.; Manna, Soumen Kanti; Robles, Ana I.; Ryan, Bríd M.; Gonzalez, Frank J.; Harris, Curtis C.
Abstract: Vitamin D is an essential micronutrient required for normal physiological function and recognized for its role regulating calcium metabolism. Recent work is beginning to emerge demonstrating a role for vitamin D in chronic illnesses, such as cancer. Circulating serum levels of 25(OH)D2/3 were quantitatively measured using sensitive ultraperformance liquid chromatography coupled to tandem mass spectrometry (UPLC‐MS/MS) in 406 lung cancer cases and 437 population controls, while 1, 25(OH)2 D2/3 levels were measured in a subset of 90 cases and 104 controls using the same method, from the NCI‐MD case–control cohort. 25(OH)D3 levels were inversely associated with lung cancer status across quartiles (Q2 vs. Q1: ORadjusted  = 0.5, 95% CI = 0.3–0.8; Q3 vs. Q1: ORadjusted  = 0.5, 95% CI = 0.3–0.8; Q4 vs. Q1: ORadjusted  = 0.5, 95% CI = 0.2–0.9; P trend  = 0.004). Levels of 1, 25(OH)2 D3 were also inversely associated with lung cancer status (Q2 vs. Q1: ORadjusted  = 0.2, 95% CI = 0.03–0.7; Q3 vs. Q1: ORadjusted  = 0.1, 95% CI = 0.01–0.4; Q4 vs. Q1: ORadjusted  = 0.04, 95% CI = 0.01–0.3; P trend <0.0001). Although the observed trends were similar for the 25(OH)D2 ( P trend  = 0.08), no significant associations were seen between vitamin D2 and lung cancer status. Additionally, genotyping of 296 SNPs in the same subjects resulted in findings that 27 SNPs, predominantly in CYP24A1 and VDR genes, were significantly associated with lung cancer status, affected mRNA expression, and modulated vitamin D levels. These findings suggest a protective role for vitamin D3 in lung cancer, with similar trends but insignificant findings for D2 . Vitamin D3 levels appeared to be modulated by genetic variation in CYP24A1 and VDR genes. Additional research to illuminate the mechanism(s) through which vitamin D exacerbates effects against lung carcinogenesis is warranted. Abstract : Inverse association between 25(OH)D3 and hormonally active form 1, 25(OH)D3 and lung cancer was observed in a case control study. Associations between vitamin D2 and lung cancer were not statistically significant. Single nucleotide polymorphisms in CYP24A1 and VDR may modulate the observed associations.